2008
DOI: 10.1088/1748-9326/3/4/044008
|View full text |Cite
|
Sign up to set email alerts
|

Spatio-temporal variability of NDVI–precipitation over southernmost South America: possible linkages between climate signals and epidemics

Abstract: Climate-environment variability affects the rates of incidence of vector-borne and zoonotic diseases and is possibly associated with epidemics outbreaks. Over southernmost South America the joint spatio-temporal evolution of climate-environment is analyzed for the 1982-2004 period. Detailed mapping of normalized difference vegetation index (NDVI) and rainfall variability are then compared to zones with preliminary epidemiological reports. A significant quasi-biennial signal (2.2-to 2.4-year periods, or QB) for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(21 citation statements)
references
References 57 publications
0
21
0
Order By: Relevance
“…It is derived from NOAA AVHRR data, available at 15-day temporal resolution and an 8 km spatial resolution (Tourre et al, 2008). These data were used to assess the influence of vegetation on soil freeze depth.…”
Section: Ndvimentioning
confidence: 99%
“…It is derived from NOAA AVHRR data, available at 15-day temporal resolution and an 8 km spatial resolution (Tourre et al, 2008). These data were used to assess the influence of vegetation on soil freeze depth.…”
Section: Ndvimentioning
confidence: 99%
“…It can also reduce most irradiance changes relative to instrument calibration, sun angle, terrain, cloud shadow and atmospheric conditions (Tucker, 1979;Crippen 1990). Thus, the NDVI is a good proxy for evaluating the potential links of the variability in regional ecosystems and local ecotones with the spatiotemporal variability to climate conditions (e.g., Tourre et al 2008;Koepke et al 2010;Zhang et al 2013;Frost et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Satellite images from Landsat, SPOT, and IKONOS have been used to characterize and predict mosquito larval habitats (Rejmankova et al 1998, Masuoka et al 2003, Pope et al 2005, Mushinzimana et al 2006). Spatiotemporal variability of the normalized difference vegetation index (NDVI) has been positively correlated with incidence rates of vector‐borne diseases such as malaria, dengue, West Nile virus, and hence epidemic outbreaks (Brown et al 2008, Tourré et al, 2008, Ward, 2009). Studies of malaria incidence in Africa or Asia have shown their association with, or actually been modeled by, weather, rainfall, temperature, NDVI (Gomez‐Elipe et al 2007, Funk and Brown 2006, Liu and Chen 2006, Gaudart et al 2009), and by the enhanced vegetation index (Noor et al 2008).…”
Section: Introductionmentioning
confidence: 99%